2010
DOI: 10.1080/08982112.2010.505219
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Median-Rank Regression and Maximum Likelihood Estimation Techniques for a Two-Parameter Weibull Distribution

Abstract: Practitioners frequently model failure times in reliability analysis via the Weibull distribution. Often risk managers must make decisions after only a few failures. Thus, an important question is how to estimate the parameters of this distribution for extremely small sample sizes and=or highly censored data. This study evaluates two methods: maximum likelihood estimation (MLE) and median-rank regression (MRR). Asymptotically, we know that MLE has superior properties; however, this study seeks to evaluate thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…In addition, the MRR technique does not take into account the cycle number where the tests ended (593 in this case) when there are suspended tests. This, in addition to other well-known issues with MRR analysis 56,58 , motivates us to avoid the OLS-based analysis and use the maximum likelihood (ML) technique 48,56 . This involves, in effect, searching for the values of (β, η), (β, η, ), or () that maximize the likelihood of the associated pdf, where likelihood is defined as the probability that a given combination of parameters would produce the observed vector of failure times.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MRR technique does not take into account the cycle number where the tests ended (593 in this case) when there are suspended tests. This, in addition to other well-known issues with MRR analysis 56,58 , motivates us to avoid the OLS-based analysis and use the maximum likelihood (ML) technique 48,56 . This involves, in effect, searching for the values of (β, η), (β, η, ), or () that maximize the likelihood of the associated pdf, where likelihood is defined as the probability that a given combination of parameters would produce the observed vector of failure times.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods of estimating Weibull parameters, such as the maximum likelihood estimation, method of moment and median rank regression. Olteanu and Freeman [25] studied the performance of maximum likelihood estimation (MLE) and median rank regression (MRR) methods and they concluded that the median rank regression method offered the best combination of accuracy and ease of interpretation when the sample size and number of suspensions are small. This method is very popular in industry because fitting can be easily visualized.…”
Section: Weibull Parameters Estimationmentioning
confidence: 99%
“…The parameters of Eqs. 14and (15) can be derived from historical data records using techniques such as the maximum likelihood estimation and the median-rank regression methods (Soliman et al, 2006;Olteanu and Freeman, 2010).…”
Section: Numerical Examplementioning
confidence: 99%